In‐plane Extended Nano‐coulter Counter (XnCC) for the Label‐free Electrical Detection of Biological Particles. Issue 12 (28th June 2022) - Zhao, Zheng; Vaidyanathan, Swarnagowri; Bhanja, Payel; Gamage, Sachindra; Saha, Subhrajit; McKinney, Collin; Choi, Junseo; Park, Sunggook; Pahattuge, Thilanga; Wijerathne, Harshani; Jackson, Joshua M.; Huppert, Mateusz L.; et al.
Abstract: We report an in‐plane extended nanopore Coulter counter (XnCC) chip fabricated in a thermoplastic via imprinting. The fabrication of the sensor utilized both photolithography and focused ion beam milling to make the microfluidic network and the in‐plane pore sensor, respectively, in Si from which UV resin stamps were generated followed by thermal imprinting to produce the final device in the appropriate plastic (cyclic olefin polymer, COP). As an example of the utility of this in‐plane extended nanopore sensor, we enumerated SARS‐CoV‐2 viral particles (VPs) affinity‐selected from saliva and extracellular vesicles (EVs) affinity‐selected from plasma samples secured from mouse models exposed to different ionizing radiation doses. Abstract :